MODEL DEVELOPMENT FOR INNOVATION-ORIENTED ENTERPRISE MANAGEMENT - Alexey V., Panfilov (Advanced Engineering Research, 2012)
Basic contradictions of the postindustrial period and the strategic and innovation management are r e vealed. The recommendations on the model improvement for the innovation - orie nted enterprise social management are form ulated.